1986
DOI: 10.1272/jnms1923.53.409
|View full text |Cite
|
Sign up to set email alerts
|

Congenital pyloric atresia. A report on a successfully treated case and existing research.

Abstract: Congenital pyloric atresia is a rare malformation that occurs with a frequency of about one per million births. One hundred fifty-one cases of the anomaly have been reported including 28 cases in Japan. This is a report on an additional case of membranous atresia that was treated successfully by incision of the diaphragm with pyloroplasty. The familial occurrence in siblings and the association of the abnormality with hereditary epidermolysis bullosa suggests a genetic etiology. Treatment should be surgical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Kodoma et al reported 38.8% mortality rate has been found in children with congenital web or diaphragm and mortality rate goes up if there are other gastrointestinal anomalies (92.1%) 11 . Affected neonates usually die due to respiratory distress, aspiration pneumonia, metabolic alkalosis resulting from persistent vomiting, and even gastric perforation 11 . Meckel's Diverticulum and malrotation have been found as associated anomalies during surgery in our case.…”
Section: Discussionmentioning
confidence: 98%
“…Kodoma et al reported 38.8% mortality rate has been found in children with congenital web or diaphragm and mortality rate goes up if there are other gastrointestinal anomalies (92.1%) 11 . Affected neonates usually die due to respiratory distress, aspiration pneumonia, metabolic alkalosis resulting from persistent vomiting, and even gastric perforation 11 . Meckel's Diverticulum and malrotation have been found as associated anomalies during surgery in our case.…”
Section: Discussionmentioning
confidence: 98%